Pengembangan Buku Bergambar Toleransi Beragama Kasama Weki untuk Meningkatkan Kemampuan Berfikir Kritis Siswa - Rahman, Arif; Sasmita, Lita; Adella, Adella; Fikrin, Fikrin (SENTRI: Jurnal Riset Ilmiah, 2025)
This study aims to develop the Kasama Weki illustrated book based on Dompu’s local wisdom as a learning medium that is not only visually engaging but also serves as a means to internalize religious tolerance values and strengthen critical thinking skills among elementary school students. The research employed a Research and Development (R&D) approach using the 4D model, which includes the stages of define, design, develop, and disseminate. The research subjects consisted of 25 sixth-grade students of SDN 1 Dompu in the 2025/2026 academic year. The research instruments included expert validation sheets, student response questionnaires, and critical thinking post-test items. The findings revealed that: (1) The define stage successfully identified issues of intolerance and the need for contextual learning media that integrate local cultural values; (2) The design stage produced drafts of the illustrated book, teaching module, and evaluation instruments integrated with the Project Based Learning model; (3) The develop stage resulted in a highly feasible product, with an average expert validation score of 87.6%, student response score of 88.5% (very good category), and a post-test average score of 83.7 (very good category); and (4) The disseminate stage was carried out on a limited scale involving teachers and students, as well as through scientific publication. Overall, the results indicate that the Kasama Weki illustrated book is valid, practical, and effective as a learning medium that fosters mutual respect among students of different religions and enhances critical thinking skills through contextual, culture-based learning activities. Therefore, the development of this illustrated book provides a significant contribution to educational practice and character education in elementary schools.